A Molecular Engineering Strategy for Achieving Blue Phosphorescent Carbon Dots with Outstanding Efficiency above 50%. Issue 6 (19th December 2022) - Song, Zhijiang; Shang, Yuan; Lou, Qing; Zhu, Jinyang; Hu, Junhua; Xu, Wen; Li, Changchang; Chen, Xu; Liu, Kaikai; Shan, Chong‐Xin; Bai, Xue
Abstract: Highly efficient emission has been a long‐lasting pursuit for carbon dots (CDs) owing to their enormous potential in optoelectronic applications. Nevertheless, their room‐temperature phosphorescence (RTP) performance still largely lags behind their outstanding fluorescence emission, especially in the blue spectral region. Herein, high‐efficiency blue RTP CDs have been designed and constructed via a simple molecular engineering strategy, enabling CDs with an unprecedented phosphorescence quantum efficiency of to 50.17% and a long lifetime of 2.03 s. This treating route facilitates the formation of high‐density ( n, π*) configurations in the CD π–π conjugate system through the introduction of abundant functional groups, which can evoke a strong spin‐orbit coupling and further promote the intersystem crossing from singlet to triplet excited states and radiative recombination from triplet excited states to ground state. With blue phosphorescent CDs as triplet donors, green, red, and white afterglow composites are successfully fabricated via effective phosphorescence Förster resonance energy transfer. Importantly, the color temperature of the white afterglow emission can be widely and facilely tuned from cool white to pure white and warm white. Moreover, advanced information encryption, light illumination, and afterglow/dynamic visual display have been demonstrated when using these multicolor‐emitting CD‐based afterglow systems. Abstract : Through a molecular engineering strategy, more functional groups are modified on the surface of carbon dots embedded in the rigid silica network, which not only greatly boosts the spin‐orbit coupling, improves the intersystem crossing rate, but also stabilizes the triplet excited state, resulting in efficient blue phosphorescence.